Assessment of Atherosclerotic Cardiovascular Disease Risk in Primary Prevention. Issue 6 (November 2022) - Rikhi, Rishi; Shapiro, Michael D.
Abstract : A quantitative evaluation is the foundation for assessing atherosclerotic cardiovascular disease risk in primary prevention. In the United States, the pooled cohort equations are used to calculate 10-yr atherosclerotic cardiovascular disease risk. This review focuses on the application of the pooled cohort equations and the assessment of cardiovascular health. Abstract : Purpose: The objective of this report was to review the application of the pooled cohort equations in primary prevention and the assessment of cardiovascular health. Review Methods: Literature review was conducted using the PubMed database. In addition, the 2018 Multi-Society Guidelines on Management of Blood Cholesterol and the 2019 American College of Cardiology/American Heart Association Guidelines on the Primary Prevention of Cardiovascular Disease were reviewed. Summary: Primary prevention refers to individuals with no history of atherosclerotic cardiovascular disease, severe hypercholesterolemia, or diabetes. For these adults, aged 40-75 yr, who have a low-density lipoprotein-cholesterol of ≥70 mg/dL and <190 mg/dL, the pooled cohort equations should be used to provide a quantitative assessment of 10-yr atherosclerotic cardiovascular disease risk. From here, individuals are grouped as low risk (<5%), borderline risk (5 to <7.5%), intermediate risk (7.5 to <20%), or high risk (≥20%). Statin therapy should be strongly advised in those with an atherosclerotic cardiovascular disease risk of ≥20%, while statin therapy can be considered in those with a risk between 5% and <20%, especially if risk enhancing factors are present. If uncertainty still exists regarding treatment, a coronary artery calcium score can help further refine risk. All individuals, regardless of atherosclerotic cardiovascular disease risk, should have a cardiovascular health assessment using Life's Essential 8, which includes diet, physical activity, nicotine exposure, body mass index, blood glucose, blood lipids, blood pressure, and sleep.